Psychological well-being of adolescents in Selangor, Malaysia - Nageswary Visvanathan; Mohd Nazri Abdul Rahman; Ahmad Shamsuri Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Psychological well-being is an important measure in understanding the state of happiness and satisfaction of life that leads to the achievement of full potential and optimal level of functioning that determines success among adolescents. This study aims to measure the level of psychological well-being among adolescents of secondary schools from four districts in Selangor state in Malaysia. A quantitative survey design study carried out among 252 adolescents (aged 16 years old) with a mixed sampling method. The Ryff Psychological wellbeing scales (42 items) was used as the instrument. The data was analysed via Statistical Package for Social Studies (SPSS) version 25. Findings shows that majority adolescents in Selangor have moderate level of psychological well-being. The findings of this study gives an understanding on the adolescents’ issues in Selangor. The implications of the current study for school level interventions are also discussed. In conclusion, its recommended that there should be more focused attention given to increase the level of psychological well-being among adolescents.